Cardiac Disease in Pregnancy: Maternal and Perinatal Outcomes in RSUP Dr. Mohammad Hoesin Palembang - Ni Made Dyah Gayatri; Peby Maulina Lestari; Abarham Martadiansyah; Nuswil Bernolian; Hadrians Kesuma Putra; Rizky Agustria; Muwarni Emasrissa Latifah (HM Publisher, 2022)
Background: Impaired maternal and uteroplacental perfusion can occur in pregnancy with cardiac disease leading to maternal and perinatal mortality and morbidity due to increased cardiac load and ventricular dysfunction. This research aims to determine maternal and perinatal outcomes of pregnancies with cardiac disease. Method: This research was a descriptive observational study conducted by total sampling method and cross-sectional design. This research used medical records of pregnant women with cardiac disease who gave birth in RSUP Dr. Mohammad Hoesin Palembang in January 2018-December 2020 as study samples. Result: Among 68 pregnancies with cardiac disease, there were 6 cases (0.87%) found in 2018, 38 cases (2.47%) found in 2019, and 24 cases (1.48%) found in 2020. The highest distribution of pregnancies with cardiac disease was found at 64.7% in the range of 20-35 years old age group; 57.4% in the multiparity group; 38.2% in the range of ≥34 – <37 weeks gestational age group; 86.8% in the high school educational level group; 66.2% in the high-risk cardiac functional status group; 54.4% in the peripartum cardiomyopathy group; and 36.8% with preeclampsia/eclampsia as a comorbid. In this study, maternal outcomes found were maternal mortality at 11.8%; cardiac failure at 70.6%; arrhythmia at 1.5%; and stroke at 1.5%, while perinatal outcomes found were prematurity at 60.3%; low birth weight at 64.4%; IUGR at 37.0%; IUFD at 1.4%; stillbirth at 6.8%; neonatal death at 9.6%; and perinatal asphyxia at 42.5%. Conclusion: The prevalence rate of pregnancies with cardiac disease in RSUP Dr. Mohammad Hoesin Palembang was 0.87% in 2018, 2.47% in 2019, and 1.48% in 2020. The most common maternal outcome in this study was cardiac failure, with most in the peripartum cardiomyopathy group, while the most common perinatal outcome was low birth weight, with most in the hypertensive heart disease group.